REMEDIASI MISKONSEPSI PESERTA DIDIK SMP MENGGUNAKAN LEAFLET PADA HUKUM ARCHIMEDES - Ambarwati, Virna Ayu; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to find out the effectiveness of leaflet to improve SMP Negeri 1 Siantan studentsâ€™ misconception on Archimedes principle. The method used in this research was a one-group pretest-posttest. Data collection instrument of this research was in form of multiple choice tests without reason. This research involved 31 students from VIII A as the sample which selected through intact group, which is the whole sampling based on a group of population. From 31 students who followed remediation, the result showed decreasing percentage of students misconception in all indicators by 73%. Based on McNemar test calculate, obtained Â in all indicators of 36.54 then Ï‡2 hitung> Ï‡2tabel caused that there was a significant conceptual change. The effect size was 1.40 (classified high) according to Hattie (2009). This research was expected to be used by teachers as an alternative to improve students' misconception on Archimedes' principle.Keywords: Remediation, Misconceptions, Leaflet, Archimedes principleÂ